Análise da Taxa de Performance de Sistemas Fotovoltaicos instalados em uma Região Semiárida - Vieira, Romênia (Latin American Journal of Energy Research, 2025)
Encouraging the use of renewable energy sources has led to an increase in the installed capacity of grid-connected photovoltaic systems all over the world. Evaluating the performance of such systems is important to identify whether they are working properly or whether there are losses in the system. In this sense, the performance ratio, plays a fundamental role in determining the behavior of systems, considering the various sources of losses. It is also essential for helping to design and implement photovoltaic systems. Therefore, this study aims to analyze the performance ratio of 106 grid-connected photovoltaic systems and located in the Brazilian semi-arid. Once the analysis was complete, it was possible to determine the monthly and annual performance of each photovoltaic plant analyzed. This study highlights the importance of evaluating the systems implemented in the region and provides valuable information for implementing new systems